Effect of a Hospital-Acquired Pressure Injury (HAPI) Risk Score on HAPI Rates in Patients With Vascular Diseases. Issue 1 (January 2023) - Moyse, Tonya; Bates, Jacqueline; Bena, James F.; Morrison, Shannon L.; Albert, Nancy M.
Abstract : PURPOSE: The purpose of this study was to assess whether a validated hospital-acquired pressure injury (HAPI) risk scale and best practice interventions were associated with lower HAPI rates compared with previous care. We also sought to identify a cut score of HAPI risk when using the instrument. DESIGN: Nonequivalent 2-group pre- and postintervention comparative study. SUBJECTS AND SETTING: The sample comprised 2871 patients treated for vascular diseases; data were collected on 2674 patients before the intervention and 197 patients postintervention. Their mean (SD) age was 69.3 (12.4) years; 29.3% (n = 842) had a history of diabetes mellitus. Based on discharge status, more patients received home health care after discharge in the postintervention group, 34% (n = 67/197) versus 16.2% (n = 430/2662), P = .001. The study setting was a quaternary care hospital in the Midwestern United States. METHODS: Patients who were at high risk for HAPI, based on a nomogram score, received a mobility and ambulation program intervention. Pre- and postintervention cohorts were compared using analysis of variance, χ 2 test, and Fisher exact test. A receiver operating characteristic curve plot was generated to determine the ability of the risk score tool to identify HAPI risk at all possible cut points. RESULTS: Despite differences in patient characteristics, primary medical diagnosis, and postdischarge health care needs, the HAPI rate decreased postintervention from 13.8% (n = 370/2674) to 1.5% (n = 3/197), P = .001. A HAPI risk-predicted value cut score of 18 had strong sensitivity (0.81) and specificity (0.81), and positive and negative predictive values of 0.42 and 0.96, respectively. CONCLUSION: Despite higher patient acuity during the intervention period, HAPI rate decreased after HAPI nomogram and nurse-led mobility intervention implementation.